2010
DOI: 10.1186/1471-2202-11-103
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy is related to theta band brain connectivity and network topology in brain tumor patients

Abstract: BackgroundBoth epilepsy patients and brain tumor patients show altered functional connectivity and less optimal brain network topology when compared to healthy controls, particularly in the theta band. Furthermore, the duration and characteristics of epilepsy may also influence functional interactions in brain networks. However, the specific features of connectivity and networks in tumor-related epilepsy have not been investigated yet. We hypothesize that epilepsy characteristics are related to (theta band) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
115
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(126 citation statements)
references
References 51 publications
9
115
0
2
Order By: Relevance
“…It has been found that seizure semiologies characterized by impaired consciousness demonstrate abnormal slow-wave activity (Yang et al 2012). Theta band connectivity has also been proposed as an early diagnostic test for epilepsy (Douw et al 2010a), and pathologically elevated theta connectivity has related to greater seizure frequency (Douw et al 2010b). Finally, a treatment of epilepsy, vagus nerve stimulation, has previously been shown to increase and decrease gamma and theta band connectivity, respectively, underscoring the potential relevance of our findings for seizure control (Marrosu et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that seizure semiologies characterized by impaired consciousness demonstrate abnormal slow-wave activity (Yang et al 2012). Theta band connectivity has also been proposed as an early diagnostic test for epilepsy (Douw et al 2010a), and pathologically elevated theta connectivity has related to greater seizure frequency (Douw et al 2010b). Finally, a treatment of epilepsy, vagus nerve stimulation, has previously been shown to increase and decrease gamma and theta band connectivity, respectively, underscoring the potential relevance of our findings for seizure control (Marrosu et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…19,20,34,35 An increase in theta band functional connectivity was associated with seizure frequency in tumor-related epilepsy. 36 One could speculate that increased functional connectivity in epilepsy is somehow a protective mechanism against seizure generation, which fails in a stress-sensitive subset of subjects as cortisol increases. There is evidence for the hypothesis that desynchronization takes place accompanied by a reduction of IEDs prior to seizure onset.…”
Section: Cortisol and Functional Connectivitymentioning
confidence: 99%
“…In essence, the strength of connections among network nodes and their directionality may define for us the extent of epileptogenic territory. An altered functional connectivity has been proposed in the case of both mesial temporal lobe epilepsy [14] and tumour-associated epilepsy [15] patients. A pathologically increased theta or low frequency band connectivity was found to be related to increased seizure activity in brain tumour patients raising some consideration as to whether such findings may shed light on peritumoural epileptogenesis.…”
Section: Neurobiologymentioning
confidence: 99%